2019
DOI: 10.1021/acs.chemmater.9b02234
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Role of Internalized Geometric Strain on Heterogeneous Electrocatalysis

Abstract: The chemistry underlying the activation of nickel hydroxide toward electrocatalytic oxygen evolution by incorporation of iron remains a subject of debate. We extract insights into the role of geometric strain on the electrochemical behavior in this class of materials by blending aluminum, gallium, or iron into a disordered nickel hydroxide lattice. The electrochemical behavior and electronic structure of the three binary composition series are found to be similarly influenced by each additive cation. Density f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…[29] The relationships between B-site disorder and Tafel slope (Figure 7C) and reaction selectivity (Figure 7D) for an extended range leads us to propose that B-site distortions caused by Fe-doping changes α by selectively distorting the coordination environments of reaction sites. Such changes in α are not yet fully understood in the literature, but they have been suggested to arise from distortions that alter the symmetry of the potential energy surface for layered double hydroxide electrocatalysts for the oxygen evolution reaction, [31][32][33] and to be controllable through lattice strain manipulation. [18,[34][35][36] The ability to systematically tune the Tafel slope through non-conventional values by simple compositional substitution identifies this family of materials, especially LaSrNi 1À y Fe y O 4 + δ , as a candidate to establish a more robust understanding on the variation of the α parameter in heterogeneous electrocatalysis.…”
Section: Discussionmentioning
confidence: 99%
“…[29] The relationships between B-site disorder and Tafel slope (Figure 7C) and reaction selectivity (Figure 7D) for an extended range leads us to propose that B-site distortions caused by Fe-doping changes α by selectively distorting the coordination environments of reaction sites. Such changes in α are not yet fully understood in the literature, but they have been suggested to arise from distortions that alter the symmetry of the potential energy surface for layered double hydroxide electrocatalysts for the oxygen evolution reaction, [31][32][33] and to be controllable through lattice strain manipulation. [18,[34][35][36] The ability to systematically tune the Tafel slope through non-conventional values by simple compositional substitution identifies this family of materials, especially LaSrNi 1À y Fe y O 4 + δ , as a candidate to establish a more robust understanding on the variation of the α parameter in heterogeneous electrocatalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Iron doping of metal oxide films has long been known to increase overall OER activity of metal oxide OER catalysts 42,43 . The behaviour of Fe in Ni-OECs has been revisited 44 , and the role of Fe has been ascribed to various factors, including active site Fe 4 + or higher valent species [45][46][47] , near neighbour Fe effects on Ni resulting from strain on the oxide lattice [48][49][50][51] , active oxygen intermediates at Ni-Fe sites [52][53][54] , Fe induced partial-chargetransfer to Ni sites 55,56 , and Fe acting as a Lewis acid that promotes charge transfer character and favourable energetics for Ni oxyl formation 57,58 . Quizzically, though detected by Mössbauer spectroscopy, the presence of Fe 4+ does not correlate with the observed catalytic activity 59 .…”
mentioning
confidence: 99%
“…The electrochemical behavior and electronic structure of Ni hydroxides are influenced by other metal ions . Smith’s group, using the density functional theory and near-infrared spectroscopy, indicated that the additive cations asymmetrically affect the voltage-induced expansion and contraction of the nickel hydroxide lattice . The peak at 1.39 V could be related to such Ni sites. …”
Section: Resultsmentioning
confidence: 99%